Expression patterns of miR-146a and miR-146b in mastitis infected dairy cattle. Issue 5 (October 2016) - Wang, Xing Ping; Luoreng, Zhuo Ma; Zan, Lin Sen; Raza, Sayed Haidar Abbas; Li, Feng; Li, Na; Liu, Shuan
Abstract: This study reports a significant up-regulation of bta-miR-146a and bta-miR-146b expression levels in bovine mammary tissues infected with subclinical, clinical and experimental mastitis. Potential target genes are involved in multiple immunological pathways. These results suggest a regulatory function of both miRNAs for the bovine inflammatory response in mammary tissue. Highlights: We identified a significant upregulation of miR-146a/b in bovine mammary tissues challenged with S. aureus or E. coli. We identified a significant upregulation of miR-146a/b in mammary gland tissues with subclinical or clinical mastitis. MiR-146a/b were not significant expression in blood from cows challenged with S. aureus or E. coli compared to healthy cows. MiR-146a/b might target on TRAF6 and IRAK1 gene, and might be involved in 20 immunological pathways. MiR-146a/b are the potential moderators of bovine mammary inflammation.